PENINGKATAN DAYA SAING UMKM MELALUI LEGALITAS USAHA DAN INOVASI PEMASARAN BERBASIS PEMBUATAN LOGO - Joni Sasmito; Putri Madinatul Munawwarah; Dini Herlina (Jurnal Pengabdian Kompetitif, 2026)
Saloloang Village in Penajam District, Penajam Paser Utara Regency has micro, small, and medium enterprises (MSMEs) that play an important role in supporting the local community’s economy. MSME actors still face challenges in improving business competitiveness, particularly in terms of business legality and strengthening visual brand identity. This community service program through the Kuliah Kerja Nyata (KKN) activity aims to improve MSME competitiveness through strengthening business legality and marketing innovation based on logo creation. The method used is a participatory descriptive approach through MSME surveys, coordination visits with the village administration, and the implementation of socialization activities for business actors. The socialization activities provide an understanding of the importance of business legality and the procedures for registering a Business Identification Number through the Online Single Submission system. The socialization activities also provide explanations regarding the concept of logos, the functions of logos, and the elements of effective logos as visual product identities. The results of the activity show an increase in MSME actors’ understanding of the importance of business legality ownership as a basis for legal protection and business development. Participants also understand the role of logos as visual identities that can strengthen product image and support promotional strategies. The findings indicate that strengthening business legality and developing visual branding can serve as strategic steps to improve MSME competitiveness in a sustainable manner